EFFECT OF HUMAN RESOURCES QUALITY ON EMPLOYEES' WORK ETHOS IN ALWAFI ISLAMIC BOARDING SCHOOL - Chotamul Fajri; Sairin; Suworo (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine whether there is an effect of the quality of human resources (X1) on the work ethic of employees at the Alwafi Islamic Boarding School (Y). The method used in this research is descriptive quantitative method. The sampling technique used is probability sampling using a saturated sample with a sample of 40 respondents. Data analysis used regression analysis, correlation coefficient analysis, and hypothesis testing. The results of this study Based on the test results obtained the value of t arithmetic > t table or 3.699 > 2.02439. Thus Ho is rejected and H1 is accepted, this shows that there is a partially significant effect between the Quality of Human Resources (X) and Work Ethic (Y) at the Islamic Boarding School AL Wafi Islamic Boarding School. The level of quality (Education, skill.